Language structure shapes visual cognition: the effect of zoom-in vs. zoom-out presentation on visual preferences - Sugitani, Yoko; Togawa, Taku; Karasawa, Minoru (Frontiers in Language Sciences, 2026)
IntroductionThis study provides initial evidence that grammatical structure in language can shape cognitive preferences for sequential visual stimuli. Linguists classify languages as head-initial or head-final based on their syntactic headedness. Building on this typology, we propose two cognitive styles: head-initial or “zoom-out” cognition, which tends to process more specific, detailed information before focusing on broader perspectives, and head-final or “zoom-in” cognition, which focuses on information from comprehensive to specific. We hypothesized that people's cognitive styles (zoom-in vs. zoom-out) are contingent on their language type (zoom-in or zoom-out language), which determines their cognitive preferences for the order of sequential visual stimuli.MethodsWe conducted three experiments (N = 823) involving speakers of zoom-in and zoom-out languages to test our hypotheses using a single sequential visual item and questionnaire-based assessments of processing fluency. This design allowed us to isolate the cognitive effect while acknowledging limits on generalizability.ResultsAcross studies, speakers of zoom-in (zoom-out) languages tended to experience higher processing fluency and more favorable evaluations when sequential visual stimuli were presented in a zoom-in (zoom-out) style.DiscussionThese findings offer preliminary evidence linking language structure to visual cognition and highlight opportunities for future research on cross-linguistic variation in cognitive style.